Effect of Cash Flow Statement on Profitability of Nepalese Commercial Banks - Patel, Sujata (Nepalese Journal of Finance, 2024)
The study examines the effect of cash flow statement on the profitability of Nepalese commercial banks. Return on assets and net interest margin are selected as the dependent variables. The selected independent variables are share capital, cash flow from operating activities, cash flow from financing activities, cash flow from investing activities, reserve and cash and cash balance. The study is based on secondary data of 10 commercial banks with 100 observations for the period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of cash flow activities on the profitability of Nepalese commercial banks. The study showed that cash flow from operating activities has negative effect on return on assets and net interest margin. It shows that increase in cash flow from operating activities leads to decrease in return on assets and net interest margin. Similarly, cash flow from financing activities has negative impact on return on assets and net interest margin. It shows that increase in cash flow from financing activities leads to decrease in return on assets and net interest margin. However, cash flow from investing activities has positive impact on return on assets and net interest margin. It shows that increase in cash flow from investing activities leads to increase in return on assets and net interest margin. Moreover, cash and cash balance have negative impact on return on assets. It shows that increase in cash and cash balance leads to decrease in return on assets.